Trade policies to promote the circular economy A case study of lithium-ion batteries - Moïsé, Evdokia (OECD Publishing, 2023)
Affordable and sustainable lithium-ion batteries are key to the development of electric vehicles markets and to the green energy transition. Circular economy solutions for end-of-life batteries can help address primary inputs disruptions, while reducing environmental costs associated with the mining of these inputs or with battery production. Circular value chains would also help address waste and disposal problems as Li-ion batteries reach end of life. These chains are in their infancy, as complex battery designs, material chemistries and insufficient waste stocks hamper their viability, but the projected growth should support profitability. International trade in Li-ion batteries waste will remain essential in markets where domestic waste streams are insufficient to achieve the scale necessary for economically viable recycling, or where inadequate infrastructure imposes reliance on recycling capacities abroad. Promoting circular value chains for Li-ion batteries would require greater clarity on the status of these batteries as waste, consistency of transport and storage safety regulations, trade facilitation and harmonisation of standards for battery design, and regulatory targets for waste collection and recycling rates, coupled with stewardship and take-back schemes
Keywords: Energy; Environment; Trade